rtfMRI neurofeedback interventions are not cost prohibitive - Kymberly D. Young (Psychiatry Research Communications)
Evidence is accumulating that real-time fMRI neurofeedback is an effective treatment for various psychiatric disorders, including major depressive disorder (MDD). However, it is often dismissed as too expensive to ever be available clinically. This special communication compares the cost of real-time functional magnetic resonance imaging neurofeedback to both standard and novel interventions for MDD.While SSRI medications remain the most inexpensive treatment option, all other available treatments for major depressive disorder cost as much or more than a course of fMRI neurofeedback. It is concluded that rtfMRI neurofeedback is not cost prohibitive and should not be dismissed for this reason.